2015
DOI: 10.1007/s00277-015-2509-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial on the effectiveness of an intervention to treat psychological distress and improve quality of life after autologous stem cell transplantation

Abstract: Psychological distress contributes to impaired quality of life in hematological cancer patients. Stepped care treatment, in which patients start with the least intensive treatment most likely to work and only receive more intensive interventions if needed, could improve distress. We aimed to evaluate the outcome of stepped care treatment on psychological distress and physical functioning in patients treated with autologous stem cell transplantation for hematological malignancies. In the present study, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 38 publications
3
78
1
2
Order By: Relevance
“…The most frequently tested interventions in randomized clinical trials include exercise (148, 157161), cognitive behavioral therapy (149, 152, 162), and mind-body practices with stress management (161, 163165). Multiple randomized trials of these interventions have shown small to moderate benefits in improving HRQOL, and reducing fatigue and psychological distress in HCT recipients.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently tested interventions in randomized clinical trials include exercise (148, 157161), cognitive behavioral therapy (149, 152, 162), and mind-body practices with stress management (161, 163165). Multiple randomized trials of these interventions have shown small to moderate benefits in improving HRQOL, and reducing fatigue and psychological distress in HCT recipients.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 136 RCTs that met the inclusion criteria for the POLARIS study in the original search, 59 RCTs evaluated the effects of PSI, and 2 RCTs that evaluated the effects of physical activity combined with PSI also included a third study arm with PSI only (Figure ). PIs of 22 of the 61 eligible RCTs (response 36%) shared their data. In 1 RCT focusing on hematological cancer, we excluded patients who followed watchful waiting only ( n = 23), as they did not fit into one of the intervention categories.…”
Section: Resultsmentioning
confidence: 99%
“…PIs of 22 of the 61 eligible RCTs (response 36%) shared their data. In 1 RCT focusing on hematological cancer, we excluded patients who followed watchful waiting only ( n = 23), as they did not fit into one of the intervention categories. In 1 RCT that included patients with mixed cancer types, we excluded patients with gastrointestinal cancer as they received PSI combined with nutritional support ( n = 140).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, the majority of the clinical trials in this review included patients based on their status as a cancer patient receiving treatment, having symptoms from their cancer treatment or for the prevention of distress. In a recent study, Braamsee et al reported that patients (18.7%, N = 9/48) who dropped out of interventions did so stating that they felt they can cope well themselves …”
Section: Discussionmentioning
confidence: 99%
“…In some instances, patients even received both psychological and pharmacological treatments before being enrolled in the intervention studies. For example, 25% and 10.3% of patients received support from a mental health professional and antidepressants, making it difficult to disentangle any independent intervention benefit. In an another study, the proportion of participants taking antidepressants increased over time—from 29% at the baseline to 37% at 10 weeks of psychological intervention .…”
Section: Discussionmentioning
confidence: 99%